Local amplification of glucocorticoids in the aging brain and impaired spatial memory - Yau, Joyce L.; Seckl, Jonathan R. (Frontiers in Aging Neuroscience, 2012)
The hippocampus is a prime target for glucocorticoids (GCs) and a brain structure particularly vulnerable to ageing. Prolonged exposure to excess GCs compromises hippocampal electrophysiology, structure and function. Blood GC levels tend to increase with ageing and correlate with impaired spatial memory in ageing rodents and humans. The magnitude of GC action within tissues depends not only on levels of steroid hormone that enter the cells from the periphery and the density of intracellular receptors but also on the local metabolism of GCs by 11ß-hydroxysteroid dehydrogenases (11ß-HSD). The predominant isozyme in the adult brain, 11ß-HSD1, locally regenerates active GCs from inert 11-keto forms thus amplifying GC levels within specific target cells including in the hippocampus and cortex. Ageing associates with elevated hippocampal and neocortical 11ß-HSD1 and impaired spatial learning while deficiency of 11ß-HSD1 in knockout mice prevents the emergence of cognitive decline with age. Furthermore, short-term pharmacological inhibition of 11ß-HSD1 in already aged mice reverses spatial memory impairments. Here, we review research findings that support a key role for GCs with special emphasis on their intracellular regulation by 11ß-HSD1 in the emergence of spatial memory deficits with ageing, and discuss the use of 11ß-HSD1 inhibitors as a promising novel treatment in ameliorating/improving age-related memory impairments.